Control of potato purple top in Ecuador: Evaluation of CGIAR contributions to a policy outcome trajectory - Douthwaite, Boru (International Potato Center, 2020)
The purpose of this case study is to generate evidence and lessons learned on the contributions of CGIAR to stimulate policy changes to create an enabling environment for agri-food systems innovation by pursuing four objectives: 1. To determine and document how and in what ways CGIAR interventions contributed to the control of PMP in Ecuador; 2. To identify other major actions/factors that contributed to PMP control trajectory; 3. To generate findings to strengthen CGIAR contributions to PMP control trajectory; 4. To contribute to a synthesis document that compares and contrasts the ways in which CGIAR actions have influenced policy in four cases.